The Limited Job Prospects of Displaced Workers: Evidence from Two Cities in China - Betcherman, Gordon (2012)
The economic restructuring in China over the past decade has resulted in displacement of millions of workers who had been employed in the state sector. This has posed tremendous challenges economically, socially, politically, and culturally. For several years, Chinese policies attempted to cushion the shock by requiring state-owned enterprises to provide living allowances and reemployment services to workers who had been displaced. There have been few empirical studies that have tracked the experiences of these displaced or xiagang workers. This study uses survey data from two large industrial cities covering the period 1998-2000 to analyze the labor market situation of over 2,000 workers 2 years after they had been observed as displaced and unemployed. The findings point to the high rates of labor force withdrawal and a low proportion who find another wage job in the formal sector. It also documents the large number of workers who find work in the informal sector which seems to act as an important safety net. Not surprisingly, education is an important determinant of post-layoff labor market outcomes. Active labor market interventions do not seem to make a substantial difference although there is some evidence from the duration analysis that training does help workers find employment more quickly than they would have otherwise.